Concept Design of Space-Borne Radars for Tsunami Detection - Galletti, Michele; Krieger, Gerhard; Marquart, Nicolas; Börner, Thomas; Schulz-Stellenfleth, Johannes; Zink, Manfred (International Geohazards Week, 2007)
After the 2004 Boxing Day tsunami, the Ministry of Education and Research of Germany (BMBF) sponsored the GITEWS project (German Indonesian Tsunami Early Warning System), aiming at implementing an operational and effective life-saving system for Indonesia and possibly other littoral countries of the Indian Ocean. The German Aerospace Agency (DLR) is one of the many international institutions involved in the project and the Microwave and Radar Institute (DLR-HR) is committed to the development of new radar-based concepts for tsunami detection. NESTRAD, (NEar-Space Tsunami Radar) consists of a real aperture phased array radar nested inside a stratospheric airship meant to provide early warning from earthquake or landslide-generated tsunamis. It relies on three principles of detection and three corresponding operating modes, namely Altimeter Mode, Doppler Mode and Scatterometer Mode. The first mode detects relative changes in sea surface height, the second detects tsunami-induced orbital velocities, while the third detects tsunami-induced radar cross section modulations. The novelty of the concept resides however in the sensor platform. For early-warning purposes and high Doppler accuracy, continuous monitoring and therefore a stationary platform is needed. Space geostationary orbits lie very far away, at about 37000 km from the earth surface, but stratospheric geostationary platforms are being developed both in Germany (Zeppelin Luftshifftechnik GmbH) and the US (HAA, High Altitude Airship by Lockheed Martin). These are unmanned, lighter-than-air vehicles located right above the jet stream at 20 km altitude meant to provide a new and unique near-space, geostationary platform. The phased-array antenna is accommodated inside the blimp and allows for monitoring of relatively a large area. How large is the patch of ocean surface that can actually be monitored is relevant to the success of the system and is dependent on the principle of detection offered by the sensor. Besides illustrating the three principles of detection available, we will outline some system specifications, present performance prediction calculations and consider the peculiar constraints given by using airships as radar platforms. An advantage point of this concept is that, being tsunamis relatively rare events, it is desirable for such a sensor to be useful also for other purposes. Indeed, such a system could well be designed as a multi-purpose sensor, for example for weather or ocean monitoring as well as surveillance and reconnaissance purposes.
DLR Import::2019-04-03